Crapemyrtle Bark Scale Acanthococcus (=Eriococcus) lagerstroemiae (Kuwana) (Insecta: Hemiptera: Eriococcidae) - Matthew Borden; Xavier Martini; Adam G. Dale (EDIS)
The crapemyrtle bark scale is an invasive felt scale in the family Eriococcidae (or Acanthococcidae, as the taxonomy of this family is still being debated). This group is in the superfamily Coccoidea (scale insects) and the order Hemiptera (true bugs). Felt scales, also called bark scales, are not considered either armored scales or soft scales. As of early 2018, crapemyrtle bark scale has not yet been reported in Florida, however, it has been found in Alabama and Georgia and is expected eventually to spread into Florida. At that time, early detection and treatment will be critical to minimize further spread within the state. Includes: Introduction - Synonymy - Distribution - Description - Life Cycle and Biology - Hosts - Damage - Management - Selected References. https://edis.ifas.ufl.edu/in1218